Zn/Sr dual ions-collagen co-assembly hydroxyapatite enhances bone regeneration through procedural osteo-immunomodulation and osteogenesis - Zhenyu Zhong (KeAi Communications Co., Ltd., 2022)
The immune microenvironment induced by biomaterials played vital roles in bone regeneration. Hydroxyapatite (HA) and its ion-substituted derivates represent a large class of core inorganic materials for bone tissue engineering. Although ion substitution was proved to be a potent way to grant HA more biological functions, few studies focused on the immunomodulatory properties of ion-doped HA. Herein, to explore the potential osteoimmunomodulatory effects of ion-doped HA, zinc and strontium co-assembled into HA through a collagen template biomimetic way (ZnSr-Col-HA) was successfully achieved. It was found that ZnSr-Col-HA could induce a favorable osteo-immune microenvironment by stimulating macrophages. Furthermore, ZnSr-Col-HA demonstrated a procedural promoting effect on osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) in vitro. Specifically, the osteo-immune microenvironment acted as a dominant factor in promoting osteogenic gene expressions at the early stage through OSM signal pathway. Whereas the direct stimulating effects on BMSCs by Zn2+/Sr2+ were more effectively at the later stage with Nfatc1/Maf and Wnt signals activated. In vivo study confirmed strong promoting effects of ZnSr-Col-HA on critical-sized cranial defect repair. The current study indicated that such a combined biomaterial design philosophy of dual ion-doping and biomimetic molecular co-assembly to endow HA applicable osteoimmunomodulatory characteristics might bring up a new cutting-edge concept for bone regeneration study.